Gagasan Pemikiran Pendidikan Islam Dan Gerakan Pembaharuan Oleh Abdullah Ahmad - Aszmi Farida; Hanifa Hanifa; Gusmaneli Gusmaneli (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to find out the idea of ​​renewing Islamic education by Abdullah Ahmad. The method used in this research is the Systematic Literature Review (SLR) method. This research data was taken from the Google Scholar database. The author used Google Scholar as the main source of information by analyzing documents related to the idea of ​​renewing Islamic education by Abdullah Ahmad. The results of this research show that first, the curriculum according to H. Abdullah Ahmad is that there is no separation between general knowledge and religious knowledge, the two must be balanced, not separated. Second, effective learning methods according to H. Abdullah Ahmad, namely; (a) debating club method, (b) praise and punishment method, (c) play and recreation method. Third, the learning media offered by H. Abdullah Ahmad uses a system of using tables, chairs and whiteboards in the learning process. Fourth, Media, the use of print media as a learning medium according to H. Abdullah Ahmad is also necessary so that the educational message reaches the learning objectives. Fifth, Education Cost Budget. With the change to HIS, Adabiyah succeeded in getting subsidies from the Dutch colonial government